Functional gastrointestinal disorders in children: a single centre experience - Amela Selimović; Nina Mekić; Selma Terzić; Almira Ćosićkić; Evlijana Zulić; Majda Mehmedović (Medicinski glasnik, 2023)
Functional gastrointestinal disorders in childhood (FGIDs) constitute a significant time-consuming clinical problem for healthcare practitioners, and they carry an important psychosocial burden for patients and their families. The aim of this study was to characterize etiology, clinical features, and interventions in a paediatric cohort of patients with FGIDs, who were referred to a tertiary care university-affiliated centre. Methods: A retrospective study of children aged 1-15 years old referred to the Clinic for Children’s Diseases, University Clinical Center Tuzla, from January 2022 to December 2022, who fulfilled criteria for FGIDs (n=209), were divided in three groups: 0-3, 4-10 and 11-15 years old. Demographic characteristics, number of examinations, duration of symptoms, initial diagnosis, hospital evaluation and outcomes of each child were collected. Results: During the study period, 670 patients were referred to a gastroenterologist, out of whom 209 (31.2%) fulfilled the criteria for FGIDs, with median age of 8.0 years. Females were predominant in all groups (p=0.0369). Children aged 4 to 10 years were significantly more frequent (p<0.0001). A median duration of symptoms was one year. Functional constipation was the most common diagnosis, 99 (47.4%), followed by functional abdominal pain not otherwise specified, 67 (37.2%), and functional dyspepsia, 25 (12.0%). Fifty-two percent of patients did not require further follow-up by the gastroenterologist. Conclusion: Although FGDIs are frequent, they are not well accepted neither among patients nor physicians. Extensive diagnostic procedures are often unnecessary and the cessation of specialized care follow-up is possible in a significant number of cases.
Keywords: abdominal pain; constipation; functional dyspepsia; irritable bowel syndrome; Rome IV